249 PHENYLEPHRINE-INDUCED CARDIAC HYPERTROPHY IS BOTH INHIBITED AND REVERSED BY ACTIVATION OF PEROXISOMAL PROLIFERATOR-ACTIVATED RECEPTOR-ALPHA. (10th December 2015) - Robinson, P. F.; Eng, M.; Long, C. S.
Abstract : Purpose: Peroxisomal proliferator-activated receptor-alpha (PPAR-alpha) is a ligand-activated transcription factor that has been implicated in playing a role in hypertrophic signaling processes. Activation of PPAR-alpha has been shown to inhibit the hypertrophic response of cardiac myocytes to certain hypertrophic agonists. However, its role in reversing this hypertrophic response once it has been initiated has not been explored. Methods: Neonatal rat ventricular myocytes (NRVM) were prepared from one-day old rats and plated at low density in MEM with 5% calf serum. Twenty-four hours later, medium is changed to serum-free MEM with supplements. Cells were then treated with 10μM of fenofibrate or carrier for the "inhibition" experiments. After 1 hour, cells were then treated with phenylephrine (PE) at 10μM. 48 hours later, cells were evaluated for the degree of hypertrophy. For the experiments evaluating reversal of hypertrophy, we varied the timing of PE and fenofibrate with addition of PE first, followed by addition of fenofibrate 24 hours later. Following another 24 hours of exposure, cells were evaluated for the degree of hypertrophy. Cell hypertrophy was assessed using a radiolabeled protein synthesis (RLP) assay. Results: Fig 1, 2 : RLP of NRVM showing inhibition of hypertrophic response to PE. Fig 1 with fenofibrate added 1 hr prior to PE and Fig 2 with fenofibrate added 24 hrs after addition of PE, followed by 48 and 24 hrs of further exposure, respectively. (+P=NS v Control, *P=0.02 v PE). Conclusions: Fenofibrate, a PPAR-alpha agonist, is able to inhibit as well as reverse the hypertrophy induced by the exposure of neonatal rat ventricular myocytes to phenylephrine.